Quercetin Targets Cysteine String Protein (CSPα) and Impairs Synaptic Transmission - Xu, Fenglian (Public Library of Science, 2010)
BACKGROUND: Cysteine string protein (CSPα) is a synaptic vesicle protein that displays unique anti-neurodegenerative properties. CSPα is a member of the conserved J protein family, also called the Hsp40 (heat shock protein of 40 kDa) protein family, whose importance in protein folding has been recognized for many years. Deletion of the CSPα in mice results in knockout mice that are normal for the first 2–3 weeks of life followed by an unexplained presynaptic neurodegeneration and premature death. How CSPα prevents neurodegeneration is currently not known. As a neuroprotective synaptic vesicle protein, CSPα represents a promising therapeutic target for the prevention of neurodegenerative disorders. METHODOLOGY/PRINCIPAL FINDINGS: Here, we demonstrate that the flavonoid quercetin promotes formation of stable CSPα-CSPα dimers and that quercetin-induced dimerization is dependent on the unique cysteine string region. Furthermore, in primary cultures of Lymnaea neurons, quercetin induction of CSPα dimers correlates with an inhibition of synapse formation and synaptic transmission suggesting that quercetin interfers with CSPα function. Quercetin's action on CSPα is concentration dependent and does not promote dimerization of other synaptic proteins or other J protein family members and reduces the assembly of CSPα:Hsc70 units (70kDa heat shock cognate protein). CONCLUSIONS/SIGNIFICANCE: Quercetin is a plant derived flavonoid and popular nutritional supplement proposed to prevent memory loss and altitude sickness among other ailments, although its precise mechanism(s) of action has been unclear. In view of the therapeutic promise of upregulation of CSPα and the undesired consequences of CSPα dysfunction, our data establish an essential proof of principle that pharmaceutical agents can selectively target the neuroprotective J protein CSPα.